Older People, Loss, and Loneliness: The Troublesome Nature of Increased Contact With Adult Children. (July 2020) - Hagan, Robert J.; Taylor, Brian J.; Mallett, John; Manktelow, Roger; Pascal, Jan
Older people may experience considerable loss when they endure emotional or social loneliness. Emotional loneliness is related to the loss or absence of a confidant while social loneliness describes the discrepancy between the nature of one's desired and actual social network. In this article, both concepts are examined in relation to new attendees at time-limited day center reablement programs in Northern Ireland. Using group work activities, reablement programs aim to motivate participants to continue to live independently, often in the face of later life losses. Out of a total of 91 initial respondents (range, 61–94), 13 lived with adult children (10 of whom were lone parents). Those living with, or who had daily contact with, adult children had significantly higher levels of emotional loneliness at the start of their program, but not at the end. For this sample, reductions in emotional loneliness in certain cohorts of older adults who attend these programs have been identified. In conclusion, it is proposed that fourth age losses mediate older people's living arrangement and may create greater vulnerability to emotional loneliness in those living with adult children. In addition, social groups may be effective in helping reduce emotional loneliness.